Top management role in improving the state of QMS under the influence of employee's involvement: Best practice from the food processing industry - Marija Stanojeska; Robert Minovski; Bojan Jovanoski (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: The role of the top management in Quality Management System (QMS) is undeniable and emphasized by many researchers. On the other hand, the employees' involvement is recognized as one of the main prerequisites for improvement of QMS. Although investigated to a certain extent, the influence of the top management and the employees' involvement on the successful transition from ISO 9001 QMS to TQM is still a vague area. The main objective of the presented research is to investigate the influence of top management commitment on the state of QMS, through optimal management of employees' motivation. Design/methodology/approach: In order to identify the influential factors, a comprehensive literature survey was conducted, followed by survey of the companies in the food industry in the Republic of Macedonia. The selected influential factors on QMS and employee motivation are used as initial set of variables for creation of the dynamic model. Findings: As a result, the findings demonstrate how the top management can influence on the state of QMS and implementation of TQM practices in a shorter period of time. In that sense, numerous experiments with SD model have been carried out and most appropriate ratio of coefficient of commitment of top management has been determined. Originality/value: The model represents a kind of a platform for further analysis in direction of improvement the QMS towards the TQM under the influence of employees' motivation.
Keywords: 650; QMS; TQM factors; employee involvement; employee motivation; system dynamics